2012
DOI: 10.1002/uog.11152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of concomitant anterior vaginal reconstructive surgery on transobturator suburethral tape procedures

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The objective and subjective cure of SUI was 90.0% versus 86.0% and 78.9% versus 80%, respectively. This study showed consistent short‐term outcomes with other studies who had SSF with TOT either with AC or in combination with TVM although the study by Huang et al . (2012) only reported 3 months of follow‐up.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The objective and subjective cure of SUI was 90.0% versus 86.0% and 78.9% versus 80%, respectively. This study showed consistent short‐term outcomes with other studies who had SSF with TOT either with AC or in combination with TVM although the study by Huang et al . (2012) only reported 3 months of follow‐up.…”
Section: Discussionsupporting
confidence: 91%
“…reported that concomitant prolapse surgery decreased the likelihood of surgical failure after MUS (OR, 0.6). Huang et al . on the other hand, reported similar short‐term postoperative SUI rates, SUI severity and SUI‐related QoL scores among women who had received TOT procedures in isolation or in combination with either anterior colporrhaphy or TVM procedures.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Consistent with the findings of Huang et al [21], the success rate of treating SUI was comparable in the sling and sling and transvaginal mesh groups, although in ultrasound findings there was a higher incidence of proximal urethral compression from rest to straining in the women who only underwent sling surgery. We also found that a lesser compressive effect was detected in the short axis of the proximal urethra in the failed treatment group compared to the successful treatment group.…”
Section: Discussionsupporting
confidence: 89%
“…Initially there was some concern about simultaneous insertion, especially if both implants use a transobturator path. However, there are generally no technical difficulties, and the two different procedures (suburethral sling and anterior compartment mesh) seem to have very little, if any, effect on each other, as shown in a paper published in this issue of the journal. The only exception seems to be cases where both mesh and sling are inserted through the same anterior vaginal incision, which can either be deliberate or a result of inadvertent extension of one incision to the other.…”
Section: Introductionmentioning
confidence: 99%